Towards a classification strategy for complex nanostructures. Issue 4 (13th April 2017) - Castagnola, V.; Cookman, J.; de Araújo, J. M.; Polo, E.; Cai, Q.; Silveira, C. P.; Krpetić, Ž.; Yan, Y.; Boselli, L.; Dawson, K. A.
Abstract : The range of possible nanostructures is so large and continuously growing, that collating and unifying the knowledge connected to them, including their biological activity, is a major challenge. Abstract : The range of possible nanostructures is so large and continuously growing, that collating and unifying the knowledge connected to them, including their biological activity, is a major challenge. Here we discuss a concept that is based on the connection of microscopic features of the nanomaterials to their biological impacts. We also consider what would be necessary to identify the features that control their biological interactions, and make them resemble each other in a biological context.